2015
DOI: 10.5173/ceju.2015.565
|View full text |Cite
|
Sign up to set email alerts
|

Bladder injury secondary to obturator reflex is more common with plasmakinetic transurethral resection than monopolar transurethral resection of bladder

Abstract: IntroductionTransurethral resection (TUR) is the most common surgical technique for the diagnosis and initial treatment of bladder cancer. In this study, we evaluated two surgical techniques in terms of bladder injury due to obturator reflex in patients that underwent TUR for non-muscle invasive bladder cancer (NMIBC).Material and methods93 patients who underwent TUR for bladder cancer were analyzed. Fifty patients underwent monopolar resection and 43 patients underwent plasmakinetic resection. Standard TUR we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…Also, Mansour et al [9], in a controlled randomised trial, reported a 13.2% perforation rate with monopolar resection that was significantly higher than the 2.4% for bipolar resection (P = 0.02). Conversely, Ozer et al [23], reported that bladder injury was statistically significantly higher in the bipolar group, with bladder perforation seen in 10 (23%) patients vs four (8%) (P = 0.4). Furthermore, in another study, it was reported that a significant rate of obturator jerks and subsequent perforation in their first 10 patients when the power setting of the bipolar machine was adjusted to 160 and 80 W for cutting and coagulation, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Also, Mansour et al [9], in a controlled randomised trial, reported a 13.2% perforation rate with monopolar resection that was significantly higher than the 2.4% for bipolar resection (P = 0.02). Conversely, Ozer et al [23], reported that bladder injury was statistically significantly higher in the bipolar group, with bladder perforation seen in 10 (23%) patients vs four (8%) (P = 0.4). Furthermore, in another study, it was reported that a significant rate of obturator jerks and subsequent perforation in their first 10 patients when the power setting of the bipolar machine was adjusted to 160 and 80 W for cutting and coagulation, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Also, Mansour et al [9] reported a significant decrease in the incidence of nerve stimulation from 26.5% with M-TURBT vs 4.8% with B-TURBT (P = 0.01). Conversely, Ozer et al [23] reported that the obturator reflux was statistically significantly higher in B-TURBT group; with the obturator reflex observed in 15 (34%) patients vs four (8%) (P = 0.001). Also, in the Venkatramani et al [18] report, the incidence of obturator jerk was greater in the B-TURBT arm (60% vs 49.2%, P = 0.27).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…With this aim, urologists and anesthesiologists have performed obturator nerve block (ONB) using different methods. In addition, urologists use different approaches such as bipolar cautery practices, bladder wall injections, and changes of the fluid of transurethral resection (TUR) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Ozer et al [11] found a statistically significant difference in the incidence of obturator reflex and bladder perforation. In contrast to the aforementioned studies, however, they found that this complication had a higher incidence with the use of bipolar diathermy.…”
Section: Preventing “Obturator Jerk”mentioning
confidence: 99%